Influence of Solvent Concentration on the Amount of Individual Phenolic Compounds in Apple and Sour Cherry Pomace - Maria Bianca Mandache; Ana-Maria Stoenescu; Sina Cosmulescu (Horticulturae)
Apple and sour cherry pomace, by-products resulting from fruit processing for juice production, were analysed using high-performance liquid chromatography (HPLC) to identify and quantify individual phenolic compounds. In order to determine the most efficient method of extracting these phenolic compounds from pomace, different concentrations of ethanol were used as the organic solvent. The following phenolic compounds were analysed: gallic acid, neochlorogenic acid, (+)-catechin, (−)-epicatechin, chlorogenic acid, vanillic acid, caffeic acid, ferulic acid, sinapic acid, salicylic acid, ellagic acid, rutin, and myricetin. The amounts of these compounds varied depending on the concentration of ethanol used in the extraction process. Neochlorogenic acid, a potent antioxidant, was quantified in apple and sour cherry pomace extracts, showing significant variation with solvent concentration. In apple pomace, the highest amount was found in ethanol 100% (46.44 mg 100 g−1 DW), followed by ethanol 75% (32.09 mg 100 g−1 DW) and ethanol 50% (7.66 mg 100 g−1 DW). In sour cherry pomace, the highest amount was also extracted into ethanol 100% (45.20 mg 100 g−1 DW) and the lowest in ethanol 50% (29.12 mg 100 g−1 DW). Catechin was detected exclusively in cherry pomace, with a maximum yield observed in 75% ethanol (137.86 mg 100 g−1 DW), which was significantly higher compared to the other phenolic compounds analysed. The obtained results demonstrate the importance of apple and sour cherry pomace as valuable by-products, with the potential to be used in the production of functional foods.